2017
DOI: 10.1007/s12032-017-0958-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence in chronic myeloid leukaemia patients receiving tyrosine kinase inhibitors

Abstract: Failure to comply with treatment recommendations is very common in patients, but still poorly recognised by doctors. The current practice of using oral therapy on a large scale has been increasingly adopted for cancer patients. Chronic myeloid leukaemia (CML) is just such an example, where the introduction of taking new oral medications, the tyrosine kinase BCR-ABL inhibitors (TKI), has now revolutionised the treatment. The aim of our study was to assess treatment adherence in a group of Polish CML patients (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 45 publications
0
38
0
3
Order By: Relevance
“…[28][29][30] Just over one-sixth of patients switched TKI in their first year of treatment and just under one-tenth in their second year of treatment. A significant association was found between imatinib treatment and both discontinuation and switching in the first year of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] Just over one-sixth of patients switched TKI in their first year of treatment and just under one-tenth in their second year of treatment. A significant association was found between imatinib treatment and both discontinuation and switching in the first year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature does not reflect a difference in use of or response to TKIs between male and female patients, so the reason for this difference is unclear. [28][29][30] Just over one-sixth of patients switched TKI in their first year of treatment and just under one-tenth in their second year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In an international, patient‐led study (Geissler et al , ), factors associated with high adherence were older age, male sex, management of side effects, the administration of only one tablet per day, and patients feeling well informed about CML by the doctor, whereas a recent Polish study (Rychter et al , ) reported that patients over 65 years and patients with at least one comorbid disease had better adherence to TKIs. That same study also found no differences in adherence among patients treated with imatinib, dasatinib or nilotinib ( P = 0·249) (Rychter et al , ). In our study, the low proportion of non‐adherent patients meant that the association of adherence with certain possible factors could not be analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased adherence to BCR-ABL inhibitor treatment commonly occurs. 29 Although age and sex were reported as the factors for limiting adherence, adverse events induced by BCR-ABL inhibitors also decrease adherence. 30 Early detection of adverse events and adequate supportive care is useful to improve adherence.…”
Section: Discussionmentioning
confidence: 99%